2006
DOI: 10.1093/mutage/gel040
|View full text |Cite
|
Sign up to set email alerts
|

Increased cytogenetic damage in a zone in transition from agricultural to industrial use: comprehensive analysis of the micronucleus test in peripheral blood lymphocytes

Abstract: A complex situation of chemical exposure has been described in México in a zone that is in transition from rural activities towards intensive industrialization, which has brought environmental pollution: chloroform, methylene chloride, indigo and toluene are some of the pollutants found in the Atoyac and Xochiac rivers. A biomonitoring study was planned in order to establish whether there was a biological effect due to the environmental situation. Communities where leukaemia and thrombocytopenic purpura cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Only recently, endosulfan and HCH were reported to be clearly clastogenic [Tisch et al, 2005, Bajpayee et al, 2006, Jamil et al, 2004, whereas DDE was shown to be weakly genotoxic while HCB was not [Ennaceur et al, 2008]. Healthy adult individuals, nonsmokers, between 20 and 60 years old, living in Mexico City, had MN frequencies (0.6% 6 0.5) similar to those of the UCs in this study (0.78% 6 1.03); while the mothers in this study had higher MN frequencies than both of those groups (1.1% 6 0.7) (signed rank test, P 5 0.02) but lower levels (signed rank test, P 5 0.02) than nonsmoking adults (1.8% 6 1.3) living on the banks of a polluted river [Montero et al, 2006], We conclude that MN levels in the mothers can be attributable to their exposure, whereas, it appears that the UCs presented a low level of cytogenetic damage in spite of the fact that they received a large part of the load of pesticides present in the mothers' blood. We found no relationship between these biomarkers and the levels of any of the pesticides measured.…”
Section: Genotoxicitysupporting
confidence: 84%
See 1 more Smart Citation
“…Only recently, endosulfan and HCH were reported to be clearly clastogenic [Tisch et al, 2005, Bajpayee et al, 2006, Jamil et al, 2004, whereas DDE was shown to be weakly genotoxic while HCB was not [Ennaceur et al, 2008]. Healthy adult individuals, nonsmokers, between 20 and 60 years old, living in Mexico City, had MN frequencies (0.6% 6 0.5) similar to those of the UCs in this study (0.78% 6 1.03); while the mothers in this study had higher MN frequencies than both of those groups (1.1% 6 0.7) (signed rank test, P 5 0.02) but lower levels (signed rank test, P 5 0.02) than nonsmoking adults (1.8% 6 1.3) living on the banks of a polluted river [Montero et al, 2006], We conclude that MN levels in the mothers can be attributable to their exposure, whereas, it appears that the UCs presented a low level of cytogenetic damage in spite of the fact that they received a large part of the load of pesticides present in the mothers' blood. We found no relationship between these biomarkers and the levels of any of the pesticides measured.…”
Section: Genotoxicitysupporting
confidence: 84%
“…The BrdU incorporation method was used to identify proliferating cells [Serrano and Montero, 2001;Montero et al, 2006]. Whole blood samples were incubated at 378 in triplicate cultures for UC and in duplicate for mothers, in RPMI-1640 and phytohemagglutinin-M to stimulate T-lymphocyte proliferation, and 12 micromolar BrdU (final concentration).…”
Section: Micronucleus Testmentioning
confidence: 99%
“…We became interested in this subject due to the fact that these three compounds have been detected in rivers polluted with industrial waste affecting animal populations; due to their high volatility these pollutants can be spread through the air and contaminate large areas, constituting a risk of exposure for every living being around. Particularly, these polluted rivers are very close to inhabited areas of agricultural activity [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…For each individual, 2,000 binucleated cells were analysed for the presence of MN, NPBs and NBUDs in accordance with previously established criteria ( Fenech et al 2003 ). We calculated the frequency of each biomarker (number in 1,000, ‰) using the following formula: ‰ of X = (number of X/2,000) x 1,000, where X is MN, NPBs or NBUDs ( Montero et al 2006 ).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%